Incidental finding of levocardia with situs inversus: case report - Michael Stuckert, B.S.; Soumya Sharma, M.S.; Sarah Jaggernauth, B.S.; Andrew Waack, B.S.; Venkatramana Vattipally, M.D. (Radiology Case Reports)
“Situs inversus with levocardia” refers to the mirror-image lateral orientation of the abdominal organs with a normally oriented, left-sided heart. This anatomical anomaly arises from abnormalities in the biochemical signaling systems mediating embryological development. We present a case of situs inversus with levocardia incidentally discovered in a healthy 24-year-old male during workup following a motor vehicle collision. The patient had no significant prior medical history and was unknown to harbor such anatomical anomalies. Although our presented patient had no pathology associated with his anatomical abnormalities, situs inversus with levocardia is highly associated with concomitant cardiac malformations. These associated cardiac malformations are often incompatible with life, and many patients die in early childhood; nevertheless, we present a rare case of situs inversus with levocardia discovered incidentally in a healthy young adult with no associated cardiac pathology.